DISTRIBUTIVE JUSTICE FOR THE DEVELOPMENT OF TRIBAL COMMUNITY IN INDIA: POLICIES AND PROGRAMMES AS A PRE-REQUISITE FOR SUSTAINABLE DEVELOPMENT - Chengappa, Reshma (ShodhKosh: Journal of Visual and Performing Arts, 2021)
Distributive justice is concerned with the apportionment of privileges, duties, and goods in consonance with the merits of the individual and in the best interest of society is a pre-requisite for sustainable development. Primary responsibility of a state is the formulation of equitable policy and its implementation, to give justice to the weaker section of people living in the society. In India, Tribal community has been dealing with a number of issues in their daily affairs and struggling for the basic necessities of day today life which is easily accessed by others. For the governments of both union and states, tribal development has always been a matter of great concern. Non-stop effort to bridge the gap towards the way of development and sustainable growth of tribal community as a whole is the claims to have made by government. Since independence, a number of policies and programmes have been formulated in order to address the tribal issues. Yet it seems not to be enough to uplift tribal, who are living under the shadow of underdevelopment since decades. This paper makes an extensive effort to study the schemes, policies and programmes undertaken by the government of India for overall growth and development of tribal community.